PENGARUH PENGGANTIAN TEPUNG IKAN DENGAN SUSU AFKIR DALAM RANSUM TERHADAP PERFORMA PRODUKSI DAN KECERNAAN NUTRIEN AYAM BURAS JANTAN - M. E. D, PERTIWI; MASTIKA, I M.; NURIYASA, I M. NURIYASA** (Majalah Ilmiah Peternakan, 2017)
The purpose of this study is to determine the effect of fish meal substitution with expired milk in diets on the productivity of cockerels at the age of 2-10 weeks. This study was carried out in Puger Village, Jember Regency, East Java. A Completely Randomized Design (CRD) was used with five treatments and five replicates. Totally, there were 25 experimental units and each unit consists of four cockerels fed without fish meal (R0); 25% diets of fish meal substitution with expired milk (R1); 50% diets of fish meal substitution with expired milk (R2); 75% diets of fish meal substitution with expired milk (R3) and 100% diets of fish meal substitution with expired milk (R4). Diets and water were given ad libitum. The variables observed were performance and nutrient digestibility. It showed that cockerels fed 75% diets of fish meal substitution with expired milk (R3) produced higher final body weight and nutrient digestibility (P<0.05) compared to treatment R0, R1, R2 and R4. Treatment R3 produced 75.08% digestibility coefficient of dry ingredient and 72,21% digestibility coefficient of crude protein. It can be concluded that 75% fish meal substitution with expired milk produced better performance and nutrient digestibility compared to other treatment.